Quick Evaluation Study on Fourteen (14) Major Development Programmes in Sonebhadra District of Uttar Pradesh State Affected by Left Wing Extremism (LWE) - Programme Evaluation Organisation, Planning Commission (Planning Commission, Government of India, 2011)
The Quick Evaluation Study on Development Programmes in Sonebhadra District, Uttar Pradesh, commissioned by the Planning Commission of India, assesses fourteen major initiatives aimed at improving the socio-economic conditions of local communities affected by Left Wing Extremism (LWE). The study highlights notable advancements in education through Sarva Shiksha Abhiyan (SSA), improvements in health outcomes via NRHM and ICDS, and employment generation under MGNREGA, benefiting over 389,000 individuals, particularly women and marginalized groups. Despite these gains, the evaluation identifies significant challenges in infrastructure, including incomplete road connectivity under PMGSY, irregular electrification, and limited access to safe drinking water under RGNDWM. Implementation obstacles such as delayed fund releases, insufficient staffing, and low awareness of certain programmes impede overall effectiveness. The study recommends expanding MGNREGA coverage, accelerating road construction, increasing teacher recruitment and incentives, strengthening healthcare facilities, maintaining water sources, implementing computerized tracking for TPDS, and enhancing housing support through IAY. Overall, while development programmes have positively impacted livelihoods, the study emphasizes the need for targeted interventions, improved execution, and community engagement to further socio-economic progress and mitigate LWE in Sonebhadra.
Programme Evaluation Organisation Planning Commission Government of India New Delhi April, 2011
Programme Evaluation Organisation Planning Commission Government of India New Delhi April, 2011
Keywords: Sonebhadra District; Development Programmes; Left Wing Extremism; Education; Healthcare; Employment Generation; MGNREGA; Infrastructure; Road Connectivity; Electrification; Water Supply; Programme Evaluation